PARTISIPASI AKADEMISI DALAM PENGEMBANGAN DESA WISATA EKOLOGI AIK BUAL KECAMATAN KOPANG KABUPATEN LOMBOK TENGAH - Dwi Rizky Yuniarsih; Siluh Putu Damayanti; ulfan Mulyawan (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
The development of tourism villages requires the participation of every stakeeholder in the field of tourism, especially academics. Academics have a fairly important role in developing villages, namely contributing ideas or ideas they have. This research has a formulation of the problem of how academic participation forms in the development of the Aik Bual ecological tourism village. The purpose of this study is to describe how academic participation in the development of the Aik Bual ecological tourism village. This research uses literature studies as one of the foundations in carrying out research. By using a qualitative approach, the data collected with observation techniques, interviews and documentation. The results of observations, interviews and documentation are then analyzed by means of data reduction, data display and conclusion drawing. The results showed that in Aik Bual village, academics had participated by conducting service and research programs. The conclusion of this study is that academics have participated in accordance with the needs of the village but have not been able to continue due to unpreparedness on the part of the village in continuing the programs offered.